1727f Knowledge about adverse effects of working conditions must be used in counselling before conception and during early pregnancy. (24th April 2018) - Brand, T
Abstract : To find and use scientific evidence about the influence of working conditions on reproductive outcomes for practical use in a guideline for occupational and a website for pregnant women, parents to be, health care professionals and policy makers. We searched the literature for evidence concerning the effects of working conditions before, and during pregnancy on pregnancy outcome and development during early childhood. The working conditions with effects on pregnancy outcome were summarised in six groups: physically or mentally heavy work, shift work, chemical substances, physical factors (like noise) and infections. We looked at the following pregnancy outcomes spontaneous abortions, preterm birth, low birth weight, hypertension and congenital malformations and learning problems at early school age. Use of evidence: A practical guideline 1 was made for occupational physicians in The Netherlands (also translated in English). It can be used by physicians in advising pregnant women and women breastfeeding their child. In another report 'Preconception care: a good beginning', 2 the chapter about working conditions underlines the effect of exposure before conception on the embryo and fetus. In the third place the evidence was used on websites 3, 4 for parents to be or pregnant women and can be used for preventive measures regarding working conditions preconceptionally or during pregnancy. There is growing evidence that working conditions before and during pregnancy can increase the number and severity of pregnancy complications. There is also evidence that early intervention can prevent this increase of pregnancy complications. The available evidence has been used for a guideline for occupational physicians and on a website for parents to be in order to take preventive measures. A summary of the evidence will be presented together with examples how to use the evidence in counselling before conception and during early pregnancy.